Effects of salt intake and potassium supplementation on renalase expression in the kidneys of Dahl salt-sensitive rats. Issue 4 (February 2016) - Zheng, Wen-Ling; Wang, Jing; Mu, Jian-Jun; Liu, Fu-Qiang; Yuan, Zu-Yi; Wang, Yang; Wang, Dan; Ren, Ke-Yu; Guo, Tong-Shuai; Xiao, Hong-Yu
Renalase is currently the only known amine oxidase in the blood that can metabolize catecholamines and regulate sympathetic activity. High salt intake is associated with high blood pressure (BP), possibly through the modulation of renalase expression and secretion, whereas potassium can reverse the high salt-mediated increase in blood pressure. However, whether potassium could also modulate BP through renalase is unclear. In this study, we aim to investigate how salt intake and potassium supplementation affect the level of renalase in rats. Eighteen salt-sensitive (SS) and 18 SS–13BN rats were divided into six groups, receiving normal salt (0.3% NaCl), high salt (8% NaCl) and high salt/potassium (8% NaCl and 8% KCl) dietary intervention for four weeks. At the end of experiments, blood and kidneys were collected for analysis. mRNA level of renalase was measured by quantitative real-time PCR and protein level was determined by Western blot. We found that mRNA and protein levels of renalase in the kidneys of SS and SS–13BN rats were significantly decreased ( P  < 0.05) after high salt intervention, whereas dopamine in plasma was increased ( P  < 0.05) compared with rats received normal salt, suggesting that salt may induce salt-sensitive hypertension through inhibition of renalase expression. We also found increased mRNA level and protein level of renalase, decreased catecholamine levels in plasma, and decreased BP in SS rats treated with high salt/potassium, compared with that of the high salt SS group. Taken together, the salt-induced increase and potassium-induced decrease in BP could be mediated through renalase. More studies are needed to confirm our findings and understand the underlying mechanisms.